TEORI KEBENARAN DAN NALAR KRITIS (Analisis Komparatif Teori Bertrand Russell dan Teori Aswaja) - Alawy, Naufal; Najah, Hikmatul Lailatin; Syafi'ullah, Ahmad Alaika; Faizin, Moh. (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2023)
The article entitled Seeking the Truth and Critical Reasoning Perspectives of the Correspondence Theory of Truth Russell &; Islam Ahlussunnah contains theories of truth, life history of Bertrand Russell, theory of Russell's correspondence, theory of truth Islam Ahlussunnah, implementation, and implications and challenges of the theory. This article is compiled using qualitative research with ribrary research data collection method. As for the results of research, there are many theories that put forward the truth. But of the many theories that propose, correspondence is the theory most widely used by experts. This theory was originally created by Aristotle then developed by Russel, a figure famous for his mathematics and philosophy. This correspondence theory explains that truth is a statement that is appropriate or relevant to an existing reality. The implementation is to adjust the statement to reality. The implications of this theory are enormous for SCIENCE. But the challenge is the emergence of an error when observing an object due to lack of careful sensing or abnormal senses.